STRATEGI DINAS PARIWISATA KABUPATEN KOLAKA DI TENGAH PANDEMI COVID-19 (STUDI KOMUNIKASI PEMASARAN DALAM PENDEKATAN DESKRIPTIF) - Izki Fikriani Amir; Muhammad Idris (BADATI, 2022)
The impact of Covid-19 hit the entire Indonesian economy, one of which was the Indonesian tourism industry. As is the case with the Regency Tourism Office facing the challenges of the Covid-19 outbreak.The lack of visitors in all tourism destinations in Kolaka and the weakening of MSME income in Kolaka. This study describes how to answer the marketing communication strategy of the Kolaka Regency Tourism Office during the Covid-19 pandemic by using a qualitative descriptive method with a case study of marketing communication in a descriptive approach. The data collection technique used was in-depth interviews with key informants from the Kolaka Regency Tourism Office. The results of the research on several strategies applied during the pandemic are similar in Agus Hermawan's study, namely the promotion mix. The results have been updated following the pandemic conditions so that the most superior and reliable strategy for the Kolaka Regency Tourism Office is word of mouth marketing (WOM) and word of mouth marketing through digital or Electronic Word Of Mouth (E-WOM). This marketing is considered effective during a pandemic because of the trust, impression and positive experience by buyers of the services offered so that they are able to persuade, motivate potential customers more in deciding to buy. Other strategies as support include giving discounts, providing guides, and of course everything is implemented in accordance with health protocols